Comparative study of the chemical composition and antifungal activity of commercial brown seaweed extracts - Valverde, Silvia; Williams, Paul Luis; Mayans, Begoña; Lucena, Juan J.; Hernández-Apaolaza, Lourdes (Frontiers in Plant Science, 2022)
A sustainable agriculture and the great increase in consumers of organic products in the last years make the use of natural products one of the main challenges of modern agriculture. This is the reason that the use of products based on seaweed extracts has increased exponentially, specifically brown seaweeds including Ascophyllum nodosum and Ecklonia maxima. In this study, the chemical composition of twenty commercial seaweed extracts products used as bioestimulants were evaluated, as well as their antifungal activity against two common postharvest pathogens (Botrytis cinerea and Penicillium digitatum) from fruits. Data were processed using chemometric techniques based on linear and non linear models and the results showed that the algae species and the percentage of seaweed had a significant effect on the final composition of the products. In addition, great disparity was observed between formulations with similar labelling and antifungal effect of most of the analysed products against some of the tested pathogens. These findings indicate the need for further research.